'Forest Moss': no part of the European Neanderthal diet. (20th September 2017) - Dickson, James H.; Oeggl, Klaus; Stanton, Daniel
Abstract : In recent years, the study of Palaeolithic people has been a vigorous, productive topic, with the increasing knowledge of diet contributing significantly to the debate's liveliness (e.g. Richards2009 ; Henry et al .2010 ; Hardy et al .2012, 2016 ; El Zaatari et al .2016 ).